Design and engineering of graphene nanostructures as independent solar-driven photocatalysts for emerging applications in the field of energy and environment. Issue 3 (8th February 2022) - Samriti,; Manisha,; Chen, Zhangsen; Sun, Shuhui; Prakash, Jai
Abstract : Graphene and its derivatives are used as metal-free photocatalysts because of their fascinating optoelectronic properties which can further be improved by chemical doping for advanced functional applications in the field of energy and environment. Abstract : There is a growing interest in graphene-based solar-driven photocatalysis to resolve the energy and environmental issues because of their cost-effective synthesis and unique properties. Graphene and its derivatives have extensively been used as support for boosting the efficiency of wide band-gap semiconductor photocatalysts. However, recent studies show that these graphene-based nanomaterials can also serve as independent solar-driven photocatalysts to replace metal/metal-oxide-based solids for emerging applications. This paper deals with the importance of chemical doping in tailoring their optoelectronic/photocatalytic properties to make them excellent standalone metal-free photocatalysts. Heteroatom doping/co-doping induced structural and band-gap engineering of graphene/derivatives with an emphasis on the basic thermodynamic requirements for photocatalytic reactions have been discussed. Thereafter, applications of doped graphene nanomaterials as sole photocatalysts are described in the emerging field of energy and environment ( i.e., water splitting, pollutant degradation, and CO2 reduction), highlighting the latest development. Finally, various challenges in developing graphene-based sole photocatalysts and future perspectives are summarized.